STANDAR DAN EFEKTIVITAS PENGUPAHAN DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN PERSPEKTIF EKONOMI ISLAM (Studi Kasus Rumah Bersalin Siti Khadijah 1 Kota Makassar) - Suandi, Ervin; Suarni, Agusdiwana; BL, Muchran (Universitas Muhammadiyah Makassar, 2020)
This study aims to determine the standard and effectiveness of wages in improving employee welfare in an Islamic economic perspective. The type of research used is descriptive qualitative. The results obtained in this study are wage standards at RSIA. Sitti Khadijah was based on standards set by the company based on an assessment of the circumstances and living needs of employees and it was evident from the results of interviews conducted with several relevant informants who said that the determination of wage standards was based on company standards, and which became the benchmark the standard of remuneration is the UMP as a legal basis in paying employees. While the effectiveness of wages is not yet very effective and is still in the stage of effectiveness.in the application of future wage hopefully in effect again and form regulations that regulate both the question of effectiveness in the method of employee wageization so that the welfare of employees can be fulfilled moril or materially